Evaluasi Karakteristik Kekuatan Tanah yang Distabilisasi dengan Fly Ash - Himatul Farichah; Dio Alif Hutama; Dian Purnamawati Solin (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
High domestic consumption of coal, especially in energy sector, has raised concerns on several environmental issues in Indonesia. Large amount of coal combustion product in the form of solid waste, such as fly ash resulting from coal power plant production causes problems in its disposal since its necessity of land occupancy. Over the last decade, many researchers have put effort to solve this disposal concerns by utilizing these materials for various purposes, such as construction materials as part of circular economy. This paper presents the utilization of fly ash for soil stabilization in Surabaya. Firstly, the index properties of soil samples were determined through a series of laboratory soil test including specific gravity, unit weight, moisture content, sieve analysis and Atterberg’s limit tests. Subsequently, standard proctor test was conducted to obtain the maximum dry density and optimum moisture content of the soil samples. Using those parameters, four types of soil stabilized with fly ash samples were prepared with fly ash content based on weight of soil as follows: 0%, 5%, 10%, and 15%. Finally, unconfined compression tests were performed with cylindrical soil samples to assess the unconfined compressive strength of those samples. The results indicate that soil with fly ash content of 10% showing the highest unconfined compressive strength compared to the other variations of 0.90 kg/cm2.